Synergistic effects during co-pyrolysis of biomass and plastic: Gas, tar, soot, char products and thermogravimetric study. Issue 1 (February 2019) - Jin, Qiming; Wang, Xuebin; Li, Shuaishuai; Mikulčić, Hrvoje; Bešenić, Tibor; Deng, Shuanghui; Vujanović, Milan; Tan, Houzhang; Kumfer, Benjamin M.
Abstract: Synergistic effects of biomass and plastic co-pyrolysis on gas, tar, soot and char production and pyrolysis kinetics were studied using a fixed-bed reactor and a thermogravimetric analyzer, respectively. These pyrolysis products' yields and compositions were measured during the individual pyrolysis of biomass and plastic at 800–1100 °C, and synergistic effects were explored under non-sooty (900 °C) and sooty (1100 °C) conditions. Results shows that the soot starts to form from tar at 900–1000 °C for both biomass and plastic and that the soot from plastic pyrolysis is of greater yield and size than the biomass pyrolysis. Under non-sooty conditions, the synergistic effect of co-pyrolysis results in higher char yields but lower tar yields, while under sooty conditions co-pyrolysis inhibits the gas and soot formation, resulting in higher tar yields and different soot morphologies. The synergistic effect observed by the thermogravimetric analysis agrees with that in a fixed-bed reactor. Highlights: The synergistic effect of biomass and plastic co-pyrolysis is studied. Soot formation is studied besides of gas, tar, and char products. Co-pyrolysis decreases soot yield but increases tar yield under sooty conditions. Both fixed-bed and TGA results show increased char yields with co-pyrolysis.